The Healthy Community Neighborhood Initiative: Rationale and Design - Brown, Arleen F. (Ethn Dis, 2016)
OBJECTIVE: To describe the design and rationale of the Healthy Community Neighborhood Initiative (HCNI), a multi-component study to understand and document health risk and resources in a low-income and minority community. DESIGN: A community-partnered participatory research project. SETTING: A low-income, biethnic African American and Latino neighborhood in South Los Angeles PARTICIPANTS: Adult community residents aged >18 years. MAIN OUTCOME MEASURES: Household survey and clinical data collection; neighborhood characteristics; neighborhood observations; and community resources asset mapping. RESULTS: We enrolled 206 participants (90% of those eligible), of whom 205 completed the household interview and examination, and 199 provided laboratory samples. Among enrollees, 82 (40%) were aged >50 years and participated in functional status measurement. We completed neighborhood observations on 93 street segments; an average of 2.2 (SD=1.6) study participants resided on each street segment observed. The community asset map identified 290 resources summarized in a Community Resource Guide given to all participants. CONCLUSIONS: The HCNI community-academic partnership has built a framework to assess and document the individual, social, and community factors that may influence clinical and social outcomes in a community at high-risk for preventable chronic disease. Our project suggests that a community collaborative can use culturally and scientifically sound strategies to identify community-centered health and social needs. Additional work is needed to understand strategies for developing and implementing interventions to mitigate these disparities.